2006
DOI: 10.1128/iai.74.2.968-974.2006
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of an Oral Inactivated Whole-CellPseudomonas aeruginosaVaccine Administered to Healthy Human Subjects

Abstract: This study examines the safety and immunogenicity of an oral, whole-cell Pseudomonas aeruginosa vaccine administered to healthy volunteers. Thirty subjects received an oral dose of Pseudostat in two timed, measured doses with serological follow-up to 56 days postvaccination. Following vaccination, several individuals were identified as antibody responders for all three immunoglobulin (Ig) isotypes tested, specifically against whole-cell P. aeruginosa extract and outer membrane proteins F and I. The mean pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…5a). Specific IgA antibodies elicited by mucosal immunization are likely to play an important part in the adaptive immune system by inhibiting adhesion and colonization of bacterial pathogens, such as P. aeruginosa (Cripps et al 2006;Krause et al 2011). FI-specific IgA titers in immune site nasal washes of FI-MCS-MP-treated mice were significantly higher with earlier peaks than those in mice that did not receive the mannose-modified version of the vaccine (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…5a). Specific IgA antibodies elicited by mucosal immunization are likely to play an important part in the adaptive immune system by inhibiting adhesion and colonization of bacterial pathogens, such as P. aeruginosa (Cripps et al 2006;Krause et al 2011). FI-specific IgA titers in immune site nasal washes of FI-MCS-MP-treated mice were significantly higher with earlier peaks than those in mice that did not receive the mannose-modified version of the vaccine (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies suggested that systemic immunity, from either oral vaccination [8] or i.p. vaccination [31] with P. aeruginosa vaccine constructs, was as effective as mucosal delivery of the vaccine in a mucosal challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results of several attempts to develop a vaccine have been published, no P. aeruginosa vaccine is available. 5,[8][9][10][11][12][13] In gram-negative bacteria lipopolysaccharides and outer membrane proteins are the major antigenic components of the bacterial envelope. Because lipopolysaccharide-based vaccines might cause systemic adverse reactions, 14 due to systemic inflammation after parenteral injection, 7 outer membrane protein-based vaccines with an acceptable toxicity profile are attractive clinical development candidates.…”
Section: Introductionmentioning
confidence: 99%